HUBUNGAN SUPPORT SYSTEM KELUARGA DENGAN SIKAP IBU DALAM PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS RANOMUUT PERKAMIL KOTA MANADO (JURNAL KEPERAWATAN, 2015)
ABSTRACT: Breastfeeding (ASI) is the most important baby food, especially in the firstmonths of birth.Exclusive breastfeeding is very influential on the quality of infant health.Thefewer the number of babies exclusively breastfed, then the quality of the health of infants andyoung children will get worse, because the provision of complementary feeding which maycause indigestion which in turn causes growth retardation of children. The aim of researchto determine the relationship of the family support system with the attitude of Mother inexclusive breastfeeding in the PHC Ranomuut Perkamil Manado. The research method isanalytical observation with cross sectional study, the population of which is breastfeedinginfants 0-6 months of age who met the inclusion criteria. The study sample 45 respondentswere obtained by using purposive sampling technique.The instruments used arequestionnaire support system of family and mother attitude in exclusive breastfeeding.Research results using statistical test Chi Square test at 95% significance level (Ã¡ 0.05),then the p value = 0,000. This means that the value of p